USING CONCEPT MAPPING TECHNIQUE TO IMPROVE STUDENTS’ READING COMPREHENSION AT THE FIRST GRADE OF SMA NEGERI 7 AMBON - Stella Rose Que (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2021)
Reading is complex interaction between the reader and text. Actually reading is not a simple one, because in this skill, students do not only read a text but also try to understand the message or information about the text they learn. In reading process students must know what they get from a passage. This study was conducted to determine students’ improvement in reading comprehension by using concept mapping Technique. The result shows that this technique can be used to improve students reading comprehension of SMA Negeri 7 Ambon especially class X is successful. Although there were some problems which raised during teaching learning process but collaboration between English teacher and the writer help this study going smoothly. Through the technique the students can organize and identify information deeply in the text before they come to reading activity. Besides, this technique has good influenced in group discussion where the students can share their ideas and work actively to fill concept mapping sheet. The students also show positive responses toward Concept Mapping technique in the teaching learning process so the result in the class is more lively and enjoyable